Letter from Carl D. Duncan to Patricia Whiting, August 2, 1964 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
This letter discusses Duncan's travels in the Los Angeles area visiting family and attending a wedding. Throughout the letter his admiration for Patricia is highlighted. Duncan also inserted poetry throughout the letter.